KOMUNIKASI PEMBANGUNAN DALAM PEMBERDAYAAN MASYARAKATA OLEH APARATUR DESA DI DESA RANTAU SAKTI KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Reni Anzela; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Development communication in empowerment has been carried out since 2019 during the COVID-19 period in Rantau Sakti Village, which was formed from the ideas of village apparatus to help with the impact of covid-19. Village officials provide assistance in the form of community empowerment, namely hiding vegetables. Communication is very important in the activities of the village apparatus in providing information to the community about empowerment being held by the village apparatus. In relation to the theory of innovation diffusion, this is where the Rantau Sakti village from the village head, village apparatus, and the community really want new ideas or ideas for the village in obtaining new things that make new innovations. In this study, respondents tended to communicate less effectively to village officials. The purpose of this study was to determine the communication process in carrying out development to the community in Rantau Sakti Village, North Tambusai District, Rokan Hulu District and to determine community empowerment of farmer groups by village officials in Rantau Sakti Village, North Tambusai District, Rokan Hulu District. The method used in qualitative research is a research procedure that produces descriptive data. Qualitative research is a type of research in which the findings are not obtained through statistical procedures or other forms of calculation with the intention of understanding the phenomenon of what is experienced by the research subject. The research location is in Rantau Sakti Village, North Tambusai District, Rokan Hulu Regency. The results of this communication research have been effective, most community respondents who are involved or participate in the communication process directly communicate face to face with the communicator. Whereas in the communication process used in deliberation activities for the preparation of development program plans in empowering the Rantau Sakti Village community, it is very appropriate, namely using a two-way or participatory communication process. And the results of research on community empowerment have been successful and quite helpful for the people of the Rantau Sakti village in meeting their needs due to the impact of COVID-19 and in their daily lives.